Effectiveness Growth Performance and Feeding Efficiency of Tilapia (Oreo-chromis niloticus) Through Solid Bioslurry Feed in Floating Net Cages - Jamaluddin, Ruqayyah; Ayu, Anny Hary; St Zaenab; Masriah, Andi; Nurfadilah (Department of Aquaculture, 2025)
The biggest challenge in cultivation activities is the availability of sufficient quantities of feed with optimal nutritional content. Bioslurry is a local material from biogas production waste with good nutritional content. This research aims to determine the amount of solid bioslurry in feed composition that effectively increases fish growth and feed efficiency. This research used a complete design of 4 treatments and 3 replications (12 experimental units). The treatments tested were solid bioslurry as a substitute for corn flour, pollard flour, and fine bran with 0% (control) percentages, 5%, 10%, and 15%. The parameters observed were proximate bioslurry, specific growth rate, survival, feed efficiency, and feed conversion ratio. Data were analyzed using analysis of variance (ANOVA), followed by the W-Tuckey test. The proximate analysis of solid bioslurry shows crude protein was 5.54%, crude fiber 15.36%, BETN 7.19%, ash 34.13%, crude fat 0.53%, and water 37.25%. The best treatment is feed C with 5% bioslurry content produced growth of 31.5 g, the best feed efficiency (116.67%), and an FCR of 0.87%. In this research, information regarding feed formulations containing bioslurry can help make feed on tilapia fish raised in floating net cages for sustainable fisheries.